Efek Moral Reasoning Terhadap Niat Auditor Internal Untuk Melakukan Whistleblowing - Larasati, Meita (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
The purpose of this study is to investigate the effect of moral reasoning on the intention of internal auditors to conduct whistleblowing. The respondents in this study using purposive sampling technique. The researchers choose a sample based on individuals who have work experience as internal auditors for one year and at least 21 years old. This study used a survey method using a questionnaire. The questionnaire was distributed to 70 internal auditors who worked on State University located in Yogyakarta. However, only 56 questionnaires can be used in this study. All questionnaire were analyzed using regression analysis. This study provides empirical evidence that moral reasoning has a positive effect on the intention of internal auditor behavior to blow the whistle.